Reaction time and performance in the short sprints - Paradisis, G. P. (New Studies in Athletics, 2013)
Even though reaction time values are very small, they could differentiate final performance in short sprint races, where the margin of victory is often measured in thousandths of a second. The aim of this study was to examine the role of reaction time in performance in sprints at the elite level. Data on 60m and 100m races staged in the world`s most important competitions from 1996 to 2012, including the IAAF World Indoor Championships, the IAAF World Championships in Athletics (outdoors) and the Olympic Games were gathered from official published results. The times of 565 60m athletes (334 men and 231 females) and 1,533 100m athletes (866 males and 667 female) were analysed. The results showed no significant differences in reaction time between men and women in the 60m, whereas reaction times were shorter for men in the 100m. The analysis revealed an important association between reaction time and performance in the 60m but not in the 100m. The author recommends that athletes, both men and women, and coaches who are looking for success in the 100m should emphasise parameters of their training strategy other than improving reaction time as the means to improve overall performance.